GP263 Occurrence of clinical features and risk factors in culture positive early onset sepsis compared to no sepsis in neonates ≥35 weeks gestation. (June 2019) - Fisher, Arie; O'Sullivan, Anne; Fisher, Eyal; Doolan, Anne
Abstract : Background: Despite advances in prevention strategies the diagnosis of neonatal sepsis and clinical decision making remains challenging. Empirical antibiotic treatment is given to neonates when sepsis is suspected. However, clinical and laboratory signs are generally unspecific and most neonates who receive antibiotics are not ultimately diagnosed with sepsis. Many physicians view empirical antibiotics as the safest course of action in cases of equivocal clinical presentation. The long term effects of early gut flora modification are poorly understood but some scientists suggested this may alter activation of genes involved in modulating immune responses. This study aims to provide some insight into the level of risk associated with typical indications for neonatal septic workup at our institution. Methods: We conducted a retrospective case-control study. Infants born at ≥35 weeks gestation who received empirical antibiotics over a three months period were included along with all infants who were recorded to have culture positive sepsis in a ten year period. Three outcome groups were defined: (1) Culture positive sepsis (N=43) (2) Suspected culture negative sepsis (N=5) and (3) No sepsis (N=97). Rates of clinical symptoms and exposure to maternal and neonatal risk factors were compared. P-values were calculated using a test for equality of proportions implemented in the R programming language. Results: There was a statistically significant increase in red flag clinical features (mechanical ventilation, seizures, respiratory distress starting more than 4 hours after delivery and signs of shock) in the culture positive sepsis group compared to the no sepsis group (p < 0.01). There was no statistically significant difference in the occurrence of exposure to suspected chorioamnionitis, PROM or late prematurity. Conclusion: Respiratory distress and suspected chorioamnionitis were the most common indications for a sepsis workup but neither was significantly more common in the culture positive sepsis group. Observation and repeated evaluation may be suitable for infants with equivocal presentation. Critically ill infants with red flag clinical features and infants with a greater number of clinical symptoms should have a blood culture taken and IV antibiotics commenced without delay.